2016
DOI: 10.1007/s13277-016-5109-8
|View full text |Cite
|
Sign up to set email alerts
|

Germline mutations of BRCA1 gene exon 11 are not associated with platinum response neither with survival advantage in patients with primary ovarian cancer: understanding the clinical importance of one of the biggest human exons. A study of the Tumor Bank Ovarian Cancer (TOC) Consortium

Abstract: Germline mutations in BRCA1 gene have been reported in up to 20 % of epithelial ovarian cancer (EOC) patients. Distinct clinical characteristics have been attributed to this special EOC population. We hypothesized that mutations in different BRCA1 gene exons may differently affect the clinical course of the disease. The aim of this study was to analyze, in a large cohort of primary EOCs, the clinical impact of mutations in BRCA1 gene exon 11, the largest exon of the gene sequence encoding the 60 % of BRCA1 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…The study by Dimitrova et al73 of BRCA1 exon 11-associated OC revealed no 5-year OS benefit in this population versus the wild-type population, suggesting that all BRCA1 mutations are not equal in conveying survival advantage.…”
Section: Clinical Outcomementioning
confidence: 78%
See 1 more Smart Citation
“…The study by Dimitrova et al73 of BRCA1 exon 11-associated OC revealed no 5-year OS benefit in this population versus the wild-type population, suggesting that all BRCA1 mutations are not equal in conveying survival advantage.…”
Section: Clinical Outcomementioning
confidence: 78%
“…Growing data suggest that BRCA1 E11mut cells display a distinct partially platinum- and PARP inhibitor-resistant phenotype, and OC patients harboring BRCA1 mutations in exon 11 may not experience a BRCAness survival benefit 72,73. Similarly, BRCA1 mutations affecting RING domain function may also not display hypersensitivity to platinum or PARP inhibition 74,75.…”
Section: Key Future Research Avenuesmentioning
confidence: 99%
“…On the contrary, they did not observe a significant earlier disease onset among hypermethylated patients, but our finding is in accordance with our previous report carried out on a smaller sample population. 21,22 Regarding the tumor dissemination pattern, to our knowledge, this is the first study in which a detailed comparison between GMB or HMB and BWT OC patients' tumor spread has been analyzed. No difference in cancer distribution was observed between the groups, and this might also justify the absence of significant differences in optimal tumor debulking rates among the 3 cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 All detected mutations were compared with the Breast Core Information Database (https://research.nhgri.nih.gov/bic/) for describing the gene alterations. When a mutation was found, a second sequencing reaction with the reverse primer was performed to confirm the results.…”
Section: Brca1 Exon 11 Mutational Status Assessment In Blood Samplesmentioning
confidence: 99%
“…Some missense variants in highly conserved functional domains alter protein function, and others do not (Jeyasekharan et al, 2013, Starita et al, 2015). Some gene domains tolerate variants and others do not (Dimitrova et al, 2016, Wang et al, 2016). Some splice-site variants cause exon skipping, but others do not or cause alternate splicing that does not substantially change protein function (de la Hoya et al, 2016).…”
Section: Family-specific Variants and The Charge Towards Precision Mementioning
confidence: 99%